PENGARUH TEKNIK RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN SKALA NYERI MENSTRUASI (DISMENORE) PADA REMAJA PUTRI DI DESA PULAU JAMBU - Fira, Helena; Apriza, Apriza; Wati, Nila Kusuma (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
during menstruation or dysmenorrhea is often complained by teenage girls who have entered puberty as an uncomfortable sensation such as pain in the abdomen, cramps and pain in the waist that can interfere with daily activities. One of the non-pharmacological treatments for dysmenorrhea is progressive muscle relaxation techniques, which are very suitable for reducing dysmenorrhea pain. Purpose: This study was to determine the effect of progressive muscle relaxation techniques on the scale of menstrual pain (dysmenorrhea) in young women in Pulau Jambu village, the working area of the Kuok Community Health Center in 2020. Methods: This type of research uses a quasi-experimental method with a non-equivalent pretest-posttest plan. The sampling technique used purposive sampling with a sample size of 30 people. The data collection tool used was an observation sheet using the Numeric Rating Scale (NRS) pain scale. Data processing used univariate and bivariate analysis with the Wilcoxon Signed Rank Test with the SPSS 17 program. Results: this study shows that progressive muscle relaxation techniques have an influence on the scale of dysmenorrhea in young women in Pulau Jambu village, the working area of the Kuok Health Center in 2020 with a p value of 0.000. (